The buffering capacity of probiotic yogurt [Puferski kapacitet probiotičkih jogurta] - (:unkn) unknown (My University, 2011)
Aim: The potential buffering role of probiotic yogurt has not been investigated. The aim of the study was to determine the pH, titratable acidity of a selection of various probiotic yogurts, their buffering effects with an emphasis on the pH range in which the buffer is efficient. Material & Methods: A quantity of 25 ml of each yogurt was titrated with 1 mol/L sodium hydroxide, added gradually by 0.5 ml, until the pH reached 10 to assess the total titratable acidity - a measure of probiotic yogurt's own buffering capacity. Results: The initial pH was the lowest for Activia peach yogurt (4.40± 0.14) and the highest for Danone natural yogurt (5.29± 0.10). The buffering capacities can be listed as follows: Danone natural >Danone peach >Activia plain >Activia strawberry >Activia peach. There were no statistically significant differences observed between yogurts within any of the five groups compared as a whole with one another. (p >0.05). Conclusions: Buffering capacities of probiotic yogurts should be undermined.
Keywords: Bifidobacterium; Buffers; Probiotics; Yogurt